Prenatal Development and Function of Human Mononuclear Phagocytes - Miah, Mohi; Goh, Issac; Haniffa, Muzlifah (Frontiers in Cell and Developmental Biology, 2021)
The human mononuclear phagocyte (MP) system, which includes dendritic cells, monocytes, and macrophages, is a critical regulator of innate and adaptive immune responses. During embryonic development, MPs derive sequentially in yolk sac progenitors, fetal liver, and bone marrow haematopoietic stem cells. MPs maintain tissue homeostasis and confer protective immunity in post-natal life. Recent evidence – primarily in animal models – highlight their critical role in coordinating the remodeling, maturation, and repair of target organs during embryonic and fetal development. However, the molecular regulation governing chemotaxis, homeostasis, and functional diversification of resident MP cells in their respective organ systems during development remains elusive. In this review, we summarize the current understanding of the development and functional contribution of tissue MPs during human organ development and morphogenesis and its relevance to regenerative medicine. We outline how single-cell multi-omic approaches and next-generation ex-vivo organ-on-chip models provide new experimental platforms to study the role of human MPs during development and disease.